Development of graduate competencies for the changing workplace: the way forward - Abdul Rahman, Shukran (2014)
This paper discusses the notion of graduate competencies; issues around the competencies of graduates. It also discusses the Changing Workplace vis a vis expected graduate competencies/ employability. It also outlines the way forward in setting the roles of workforce development Institutions, including higher education institutions.